Trauma e testemunho em Dois irmãos, de Milton Hatoum - Amanda Carvalho Azevedo (2010)
The main purpose of this thesis is to investigate fictional works that can be recognized as testimonial writing or as conveying testimonial value. Terms such as testimony, testimonial genre, or testimonial literature are entailed in a theoretical trend that that has grown out of war survivors accounts and can provide support for the reading of several works of contemporary literature. These are operational concepts for the critical reading of literary works whose accounts, usually in first person and through some kind of mediation, reveal dramatic, violent or even catastrophic events, yielding a picture of oppression, trauma, loss, and, ultimately, death. Bearing this goal in mind, we propose to develop, under the testimonial perspective, a critical reading of three novels by Milton Hatoum: Dois irmãos, Relato de um certo Oriente and Cinzas do Norte. We intend to examine two of these novels, Relato de um certo Oriente e Cinzas do Norte, and to closely look into Dois irmãos, aiming to approach and identify, in these novels, their testimonial traits, that is, their characters and narrators limit-experiences. According to our hypothesis, these characters are, in general, struck by catastrophic experiences, both private and collective ones. In Hatoums narratives, the narrators and/or the characters strive to understand themselves and each other. The silence, the traces of pain, the feeling of loss, and the confrontations with the past are recurrent. Starting from our argument that Milton Hatoums novels bear testimonial value, we attempt to reckon this concept as a new critical tool to read his literary work.